Faktor Yang Berhubungan Dengan Kelelahan Kerja Perawat Di Ruang Rawat Inap RSUD Labuang Baji - Elsa Apritalia L; Suharni A. Fachrin; Ikhram Hardi S (Window of Public Health Journal, 2025)
Based on the results of previous research at Labuang Baji Hospital, Makassar, in 2022, with a sample of 54 people. The respondents who experienced work fatigue numbered 34 respondents (63.0%). The cause of nurses experiencing fatigue is many patient complaints and demands from the patient's family, making nurses tired and dizzy facing the patient's family (Ariska, 2022). This study uses a quantitative research method with a descriptive approach; the research design uses a cross-sectional study design. The population in this study were nurses in the Inpatient Installation Room at Labuang Baji Hospital, Makassar, with as many as 79 nurses. This study aimed to determine the factors related to work fatigue of nurses in the inpatient room of Labuang Baji Hospital, Makassar, in 2024. The results of the study There is a relationship between work shifts and work fatigue in nurses at Labuang Baji Hospital, Makassar, in 2024, p-value = 0.021 <0.05, there is a relationship between the length of work and work fatigue in nurses at Labuang Baji Hospital, Makassar in 2024, p-value = 0.997> 0.05. There is a relationship between workload and work fatigue in nurses, p-value = 0.013 <0.05; there is a relationship between psychosocial and work fatigue in nurses, p-value = 0.040 <0.05; there is a relationship between a work period and work fatigue in nurses at Labuang Baji Hospital, Makassar in 2024, p-value = 0.006 <0.05. Health workers must make good use of their rest time, do enough exercise and sleep, pay attention to their health conditions while working, and pay attention to the workload they do so that their bodies become more relaxed while working, thereby reducing the risk of high levels of work fatigue.